Analisis Perilaku Konsumen Dalam Keputusan Pembelian “Rice Bowl” di Kabupaten Sidoarjo - Wahyu Rochana; Agung Pribadhi; Novie Noordiana (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
The Rice Bowl (Nasi Mangkok) culinary business in Indonesia has experienced rapid growth after the COVID-19 pandemic and has become a key part of the modern food industry, meeting consumer demand for convenience and taste. Since 2020, rice bowl sales have continued to rise annually, driven by shifting consumption habits toward food delivery services like GoFood and GrabFood. Despite this trend, academic studies on the rice bowl business remain limited. Classified as convenience food, rice bowl consumption has increased by over 10% from 2019 to the projected figures in 2025. Sales volume has risen from 1.5 billion portions in 2020 to over 3 billion in 2025, with an annual growth rate of 10–15% and estimated revenues between IDR 15–20 trillion per year. With rising demand, many rice bowl brands have entered the market. However, consumers often struggle to decide which brand to choose, as purchasing decisions are influenced by multiple factors. This study analyzes consumer behavior influencing rice bowl purchasing decisions, focusing on cultural, social, psychological, and personal factors, with a case study in Sidoarjo Regency, East Java. Using an explanatory research design, the study surveyed 161 consumers across four sales locations.The F-test results show that all four variables simultaneously have a significant positive effect on purchasing decisions (at the 99% confidence level). However, the t-test results reveal that the cultural factor (X1) negatively influences purchasing decisions, while social, psychological, and personal factors have a positive impact. Among these, the psychological factor (X3) is the most dominant, highlighting the importance of consumer motivation and perception in shaping buying behavior. Enhancing this factor can support the sustainable growth of rice bowl businesses in Sidoarjo.